Effect of order on the half-metallic gap in Heusler compounds - Ozdogan, K.; Galanakis, I. (AMER INST PHYSICS, 2011)
Employing ab initio electronic structure methods we study the effect of order on the half-metallicity of Co2MnAl and Co2MnSi Heusler alloys. The occurrence of Co antisites destroys the half-metallic character, while for any degree of Mn-Al(Si) disorder the half-metallicity is preserved and the total spin magnetic moment is found to obey the Slater-Pauling behavior. In the structures, where Co atoms are nearest-neighbors, there is a region of low density of states around the Fermi level in the majority-spin band and a high degree of spin-polarization is exhibited. Thus the control and minimization of the concentration of Co impurities at antisites is imperative to achieve optimal performance of spintronic devices. Our results agree with available experimental results. (C) 2011 American Institute of Physics. [doi:10.1063/1.3642990]
Keywords: BAND-STRUCTURE; SPINTRONICS; Physics